2015
DOI: 10.11604/pamj.2015.21.246.5835
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long acting and permanent contraceptive methods utilization among married women of reproductive age groups in western Ethiopia: a cross-sectional study

Abstract: IntroductionIn Ethiopia information on the level of utilization of the long term and permanent contraceptive methods and associated factorsis lacking. The aim of this study was to understand the determinant factors of long acting and permanent contraceptive methods use among married women of reproductive age in Western Ethiopia.MethodsA community based cross- sectional study design was employed. Multi stage sampling was used to select 1003 study participants. Data was collected from April 10 to April 25,2014 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
45
4
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 8 publications
26
45
4
4
Order By: Relevance
“…Similarly, it was estimated that there are no implant users among married or in-union women aged 15 to 49 in 2015 in Iran (19). However, this finding is not consistent with those of other studies that showed higher rates of implant use in Australia, Malaysia, and Ethiopia (12,14,23,24). The relatively low frequent use of these methods can be attributed to misconceptions about implants such as difficulty in the insertion and removal of implants and feeling of carrying a heavy thing in the hand.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Similarly, it was estimated that there are no implant users among married or in-union women aged 15 to 49 in 2015 in Iran (19). However, this finding is not consistent with those of other studies that showed higher rates of implant use in Australia, Malaysia, and Ethiopia (12,14,23,24). The relatively low frequent use of these methods can be attributed to misconceptions about implants such as difficulty in the insertion and removal of implants and feeling of carrying a heavy thing in the hand.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, some studies reported housewife women were more likely to have unmet need of LAPMs (12,34,35).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Upaya dalam penyebaran informasi terhadap penggunaan MKJP dapat meningkatkan penggunaan MKJP melalui perubahan persepsi yang mempengaruhi pengetahuan terhadap MKJP (Credé et al, 2012;Shoupe, 2016). Paparan informasi yang terdapat pada televisi dan radio dapat meningkatkan sesuatu hal yang baru, mengetahui perubahan yang terjadi dalam kondisi sosial serta mendapatkan kesempatan yang lebih baik dan dapat mempengaruhi persepsi dan perilaku seseorang tentang kesehatannya (Melka, et al, 2015;Law et al, 2016) Penulis menyimpulkan bahwa paparan informasi melalui petugas kesehatan maupun layanan kesehatan erat kaitannya dengan perolehan pengetahuan terkait dengan KB dan pengetahuan terhadap MKJP. Adanya paparan dan akses informasi yang cepat, luas, dan berkembang dapat meningkatkan serta mempercepat penggunaan MKJP pada wanita usia subur.…”
Section: B Pengaruh Sikap Melalui Pengetahuanunclassified
“…Utilization of LARC was found to have significant association with women's sociodemographic and reproductive characteristics. Knowledge, attitude and previous LARCs use was also found to have significant association with its use [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%